2019
DOI: 10.1101/582312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative network modeling reveals mechanisms underlying T cell exhaustion

Abstract: Failure to clear antigens causes CD8 + T cells to become increasingly hypo-functional, a state known as exhaustion. We combined manually extracted information from published literature with gene expression data from diverse model systems to infer a set of molecular regulatory interactions that underpin exhaustion. Topological analysis and simulation modeling of the network suggests CD8 + T cells undergo 2 major transitions in state following stimulation. The time cells spend in the earlier proliferative/pro-me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…The time scale of the delay element, about 40 hours from entering 0% DO to Late hypoxia transition, is consistent with delayed translation observed in slow-growing MTB in response to nitric oxide (Cortes et al, 2017). It was recently demonstrated that delayed regulatory interactions within I-FFLs (with mutual inhibition present) produced state transitions related to T cell exhaustion, after a fixed time post-stimulation (Bolouri, 2019). As such, the delay element may function in MTB to incorporate robustness into the hypoxic response, ensuring that Late hypoxia (with large-scale expression changes) is not activated prematurely.…”
supporting
confidence: 76%
“…The time scale of the delay element, about 40 hours from entering 0% DO to Late hypoxia transition, is consistent with delayed translation observed in slow-growing MTB in response to nitric oxide (Cortes et al, 2017). It was recently demonstrated that delayed regulatory interactions within I-FFLs (with mutual inhibition present) produced state transitions related to T cell exhaustion, after a fixed time post-stimulation (Bolouri, 2019). As such, the delay element may function in MTB to incorporate robustness into the hypoxic response, ensuring that Late hypoxia (with large-scale expression changes) is not activated prematurely.…”
supporting
confidence: 76%